Chronic carriers of hepatitis B surface antigen in an endemic area for schistosomiasis mansoni in Brazil - JC Serufo; CMF Antunes; RA Pinto-Silva; R Gerspacher-Lara; AAM Rayes; SC Drummond; CMF Reis; MJ Martins; SA Mingoti; JR Lambertucci (Memorias do Instituto Oswaldo Cruz, 1998)
Data on the association of schistosomiasis and hepatitis B in field-based studies are scarce. Two areas have been selected for this study: i) Queixadinha, endemic for schistosomiasis, with a population of 693 individuals, and ii) Capão, a control non-endemic area, with 515 inhabitants. Sera of all individuals in both areas were tested for hepatitis B infection, yearly, from 1994 to 1997. In the first area hepatitis B was found in 32.1% of children up to one year old and reached a peak of 68.7% in the age range of 15 to 19 years. In the control area the prevalence of hepatitis B was under 5% up to 19 years of age and the highest prevalence was observed in adults over 45. HBsAg was detected in 9.4% of the individuals living in the endemic area for schistosomiasis and in 1.4% of the controls (OR=4.98; 95%CI=3.7-6.7). The index of chronicity of HBsAg was not statistically different in the studied areas (8.1% x 7.3%; OR = 1.09; 95%CI= 0.42-3.03), nor was it different for people with and without schistosomiasis in Queixadinha (8.7% x 7.0%). We conclude that the Schistosoma mansoni infection has not altered the course of hepatitis B in the studied area.